Examples of Culinary Diplomacy in Late Era Ottoman Diplomacy - Emrah Çetin (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Throughout history, not only have meals served people as a source of nutrition, but they also have served as both an individual and official tool of diplomatic agreement between people. In being representative of the culture and traditions of the host country, they serve to establish effective communication with the counter party, create a positive atmosphere, and strengthen relationships. Today, politicians still employ the unifying effect of meals as one of many tools of diplomacy. Since the dawn of man, many a statesman had employed this method with the intent of giving a positive impression both on friend and foe alike; Ottoman statesmen were no exception to this rule. One can observe many examples of culinary culture having been employed in diplomatic affairs towards the final years of the Ottoman Empire. When we look at banquets that Ottoman Sultans had prepared for their foreign guests, not only do we see that they had offered them the crème de la crème of delicacies highlighting Turkish culinary culture offered, we also see that had been treated to dishes from their own gastronomies as well. Ottoman Sultans had hosted many banquets because of their power to unify, both in terms of foreign and domestic politics. This study has reviewed and exemplified how culinary diplomacy had been used during the late era of Ottoman diplomacy.